Tipos documentais e sua relação com o processo decisório de uma empresa hospitalar da região de Bauru/SP - Nascimento, Natália Marinho do [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2013)
Decisions are made constantly in organizational contexts; however, a wrong decision can bring undesirable consequences for organizations. In this sense, access to organic information becomes essential considering that decreases the uncertainties of managers in relation to decision making process. In this perspective, the identification of documental types from its production provides a consistent documental cycle, which will result in the recovery of information at the time requested by managers. Based on the above it was intended to verify what documental types recurrently used in the decision making process of a hospital company in the Bauru region, Sao Paulo State. For that, we applied the method 'Case Study' of Yin. We analyzed the information type that provided more security to the decision maker during the decision making. As a result, we elaborated a systematic documental organic types most used and most relevant to the decision-making process of the company, showing that when they are defined from the production of documents, the benefits for both the professional as archivist for the organization are significant.

Decisões são tomadas constantemente em contextos organizacionais, no entanto, uma decisão errada pode trazer consequências indesejáveis para as organizações. Nesse sentido, o acesso à informação orgânica se faz essencial, tendo em vista que diminui as incertezas dos gestores em relação ao processo decisório. Nessa perspectiva, a identificação dos tipos documentais desde a sua produção, propicia um ciclo documental consistente, e que resultará na recuperação das informações no momento em que requisitadas pelos gestores. Partindo-se do exposto pretendeu-se verificar quais os tipos documentais recorrentemente utilizados no processo decisório de uma empresa do ramo hospitalar da região de Bauru, Estado de São Paulo. Para tanto, aplicou-se o método Estudo de Caso de Yin. Analisou-se o tipo de informação que proporcionava mais segurança ao decisor durante a tomada de decisão. Como resultado, elaborou-se uma sistematização dos tipos documentais orgânicos mais utilizados e mais relevantes para o processo decisório da empresa, evidenciando que quando estes são definidos desde a produção de documentos, os benefícios tanto para o profissional arquivista quanto para a organização são significativos.
Documental types and their relationship with the decision-making process of a hospital company in the region of Bauru/SP
Keywords: Tipologias Documentais; Identificação de Tipologias Documentais; Gestão Documental; Ciclo Documental; Gestão de Documentos